SUSTAINABLE PRACTICES IN THE SMALL PROPERTIES OF FAMILY AGRICULTURE: A CASE STUDY - Kesseler, Nilmar Sandro; Piccinin, Yvelise; Rossato, Marivane Vestena; Dörr, Andrea Cristina; Freitas, Luiz Antônio Rossi de; Marin, Alex (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Considering the economic and social importance, as well as by the ability to impact the environment through the use of natural resources, this study arises the problematic of which the practices adopted by the rural producers in the municipality of Santa Maria/RS allow to evidence characteristics of sustainability. From the analysis of these practices and perceptions of rural producers regarding the Brazilian environmental legislation in force, despite the importance of environmental issues, are not developing their activities in a fully sustainable way, considering that one of its pillars, the environmental, introduces areas for improvement with regards the harmony development with the social and economic variables. This factor could be obtained with appropriate waste disposal of the farms. Such results were made possible by the application of a questionnaire to rural producers agriculture in municipality of Santa Maria/RS.